A REVIEW ON THE ANTI-DIABETIC (PRAMEHAHARA) ACTION OF AN AYURVEDIC POLYHERBAL FORMULATION -NISAKATAKADI KWATHA - Anjali. P; Deepa M. S (International Journal of Ayurveda and Pharma Research, 2019)
Type 2 Diabetes mellitus is one of the major diseases affecting the population world wide. India is no exception with its 69. 1 million people affected as per current statistics. So in the current scenario, search for effective anti diabetic drugs are on the rise. The management of diabetes with modern system of medicine, inspite of many advances still remains unsatisfactory. This led to the search of safe, effective and cheaper herbal remedies. Such remedies can be explored from the huge wealth of Ayurveda which has been practice in India since centuries. One such effective anti diabetic Ayurvedic formulation that has been in use in Kerala by traditional vaidyas since long ago is Nisakatakadi kwatha. It is mentioned in one of the traditional Malayalam text, Sahasrayoga. It is a formulation consisting of 8 drugs viz. Nisa, Kataka, Amalaki, Paranthi, Lodhra, Bhadrika, Saptachakra and Ushira. In this review an attempt has been made to analyse the anti diabetic (pramehahara) action of this formulation by reviewing the pharmacological properties and the recent research updates on each of these 8 drugs by reviewing textbooks of Ayurveda and journal articles. This review also aims to familiarize this effective formulation to the Ayurvedic fraternity and to the general public.